Expanding the role of village malaria workers in Cambodia: Implementation and evaluation of four health education packages. - Mipharny Betrian; Dafne Umans; Moul Vanna; Sam Ol; Bipin Adhikari; Chan Davoeung; James J Callery; Yok Sovann; Thomas J Peto; Richard J Maude; Rob W van der Pluijm; Voeunrung Bunreth; et al. (PLoS ONE, 2023)
Background Early access to correct diagnosis and appropriate treatment is essential for malaria elimination, and in Cambodia this relies on village malaria workers (VMWs). Decreasing malaria transmission leave VMWs with diminished roles. Activities related to the control of other health conditions could keep these community health workers relevant. Methods During 2022, 120 VMWs attended training at local health centres on four health education packages: 1. hygiene and sanitation; 2. disease surveillance; 3. management of mild illness; 4. vaccination and antenatal care. All training and evaluation sessions were documented through meeting minutes, and 19 focus group discussions (FGDs) were conducted among VMWs and health centre personnel. Audio-records of FGDs were transcribed and translated in English and underwent thematic analysis. Results VMWs reported strong interest in the training and welcomed the expansion of their roles thus assuring their continued relevance. VMWs prioritized disease surveillance and management of mild illness among the available training packages because these topics were seen as most relevant. While training was considered comprehensible and important, the low literacy among VMWs was an impediment suggesting training materials need to be delivered visually. Since VMWs have limited resources, incentives could ensure that VMWs are motivated to undertake additional roles and responsibilities. Conclusions The transformation of VMWs into community health workers with roles beyond malaria is a promising approach for sustaining health care provision in remote areas. Training needs to consider the low scientific literacy, time constraints and limited resources of VMWs.